Effects of age on the survival and recovery of submerged rice (Oryza sativa L.) seedlings (Bangladesh Journal of Botany, 2010)
Post-submergence (about 100 cm water depth for ten days) survivality and recovery of rice seedlings were studied in a greenhouse experiment. Irrespective of varieties, 10 and 15-day-old seedlings barely could recover from the shock. More than 80% of 20-day-old seedlings of variety FR13A survived. With the increase of seedling age, elongation of plants decreased during submergence. The variety FR13A and BRRI dhan32 recovered considerably at the seedling age exceeding 20-day, whereas BR6110-10-2-1 and BR11 performed the same not below 40-day-old seedlings. At the higher seedling age, all the varieties maintained higher level of soluble sugar and starch both before and after submergence. During the submergence, the depletion rate of soluble sugar was more or less similar in all the varieties, but the rate of starch depletion was the lowest in FR13A. Therefore, the amount of total carbohydrate both pre- and post-submergence was higher in tolerant variety FR13A that might contribute to the better survivality and recovery ability. Key words: Rice; T. Aman; Carbohydrate content; Seedling age; Survival; Recovery DOI: 10.3329/bjb.v39i1.5522Bangladesh J. Bot. 39(1): 21-28, 2010 (June)